2019
DOI: 10.1111/mec.15050
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses to ocean acidification between populations ofBalanophyllia eleganscorals from high and low upwelling environments

Abstract: Ocean acidification (OA), the global decrease in surface water pH from absorption of anthropogenic CO2, may put many marine taxa at risk. However, populations that experience extreme localized conditions, and are adapted to these conditions predicted in the global ocean in 2,100, may be more tolerant to future OA. By identifying locally adapted populations, researchers can examine the mechanisms used to cope with decreasing pH. One oceanographic process that influences pH is wind‐driven upwelling. Here we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 95 publications
0
23
0
Order By: Relevance
“…These results contrast a study by Li et al (2016) on P. fuctata mantle tissue, which found that approximately 10-11% of genes in their microarray were differentially expressed in response to moderate or severe OA, including a tendency for up-regulation of ion transport genes and down-regulation of biomineralization genes within the severe OA treatment. It is unlikely that the lack of differential gene expression observed in the present study was the result of low statistical power due to small number of biological replicates, as a number of similar studies on marine invertebrates have observed significant gene expression responses to OA with the same number of, or fewer biological replicates (Evans et al, 2013;Li et al, 2016;Johnson and Hofmann, 2017;Griffiths et al, 2019) .…”
Section: Gene Expressionmentioning
confidence: 70%
See 2 more Smart Citations
“…These results contrast a study by Li et al (2016) on P. fuctata mantle tissue, which found that approximately 10-11% of genes in their microarray were differentially expressed in response to moderate or severe OA, including a tendency for up-regulation of ion transport genes and down-regulation of biomineralization genes within the severe OA treatment. It is unlikely that the lack of differential gene expression observed in the present study was the result of low statistical power due to small number of biological replicates, as a number of similar studies on marine invertebrates have observed significant gene expression responses to OA with the same number of, or fewer biological replicates (Evans et al, 2013;Li et al, 2016;Johnson and Hofmann, 2017;Griffiths et al, 2019) .…”
Section: Gene Expressionmentioning
confidence: 70%
“…A wide variety of marine calcifying organisms are known to mount significant transcriptomic responses to OA including; corals, urchins, pteropods and other species of oysters (Evans et al, 2013;Davies et al, 2016;Li et al, 2016;Johnson and Hofmann, 2017;Griffiths et al, 2019) . Studies of the pearl oyster Pinctada fuctata , the purple sea urchin Strongylocentrotus purpuratus , and the scleractinian coral Siderastrea siderea identified genes associated with ion transport, acid-base regulation, and biomineralization differentially expressed in response to OA (Evans et al, 2013;Evans and Watson-Wynn, 2014;Davies et al, 2016;Li et al, 2016) .…”
Section: Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…efforts indicate that corals collected in this manner represent distinct 'genets' with potentially different physiological adaptations 48,53 . There is evidence for genotypic variation in coral stress response, both at the phenotypic and molecular level 48,60,61 . When exposed to low pH (7.6) for short (2-week) or long (6-month) periods of time, some genets of L. pertusa were able to continue to calcify, while other genets experienced a net dissolution over the same timeframe 48 .…”
Section: Discussionmentioning
confidence: 99%
“…As a reasonable starting point to quantify standing genetic variation to ocean acidification, Griffiths, Pan, and Kelley () use data on the pH seascape across the range of a temperate coral (Figure a) to identify two populations that have been exposed to different extremes of pH conditions. The first population comes from a location that experiences lower pH due to a high degree of upwelling.…”
mentioning
confidence: 99%